Microstructure Characterisation of Freeze Linings Formed in a Copper Slag Cleaning Slag - Taskinen, Pekka A; Jansson, Jani; Kaskiala, Markku (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
The initial growth rate of freeze linings on water-cooled elements submerged in molten iron silicate slag is fast. The freeze lining microstructure forming on water cooled steel surface in a high-silica, slag cleaning furnace slag of a direct-to-blister copper smelter is mostly glassy or amorphous. It contains 5-30 mm magnetite crystals, very small and larger copper droplets as well as small magnetite and silicate nuclei embedded in the glassy silica-rich matrix. Chemically the formed freeze linings are more silica-rich than the slag from which they were generated. Magnetite (spinel) is the primary phase of the solidifying SCF slag but it does not form a continuous network through the freeze lining. Its strength is given by the intergranular silica-rich phase which initially is glassy or microcrystalline. Due to only partial slag reduction in the SCF process, large magnetite crystals are present in the freeze lining and seem to interact physically with copper droplets.